(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Travel and Tours Management System is an integrated and innovative system that processes related to travel and tours transactions, which are put together to form developing tours for customers, hiring new employees, logistics for the equipment to be used by the company, finances for the expenses that the company can use and administrative to serve as the main handle of the whole system. Logistic II is the management of the flow of products, information, and other resource transactions. This is the whole process for controlling the acquisition, storage, and distribution of resources. As a result, the researchers found three factors, which are PRODUCTIVITY, EFFICIENCY, and SECURITY. The implementation of the new and contemporary Travel and Tours Logistic II System, owned by Mblitz Travel and Tours, can provide more functionalities than before, including responsive web design, real-time tracking of deliveries, and more manageable collaboration between vendors and contractors. The Travel and Tours Management System Logistic II will enhance visibility in the supply chain. This will enable the company to better control costs, tease out efficiencies, spot supply chain problems, and gain insights into opportunities. It will also help to prevent loss in several ways. The company knows how many items it has on hand at any given time, can track movement and location so items won’t be misplaced without notice, and ensures the storage and transport conditions that prevent spoilage and damage. This project will use one of the most common network setups, which is the star topology. It is designed with each node like workstations, printers, laptops, servers, etc. Connected directly to the central device called a network switch. It is used because star topology is reliable; if one cable or device fails, then all the others will still work. It is also high- performing as no data collisions can occur and less expensive because each device only needs one I/O port.